Pleomorphic Adenoma in Subcutaneous Plane of the Neck: A Rare Entity - Bharat Kamath; Pooja Kamath; Prasad Bhukebag (Journal of Clinical and Diagnostic Research, 2015)
Heterotopic Salivary Gland Tissue (HSGT) is salivary tissue found in locations not normally host to it. Neoplasms occurring in these heterotopic tissues are very rare. Review of literature has revealed the neck to be host to HSGT and rarely, tumourigenic changes in these inclusions have been observed. We present a clinically unsuspected case of an ectopic pleomorphic adenoma of lower neck in which the ectopic salivary tissue was found in subcutaneous plane, which to the best of our knowledge has not been reported and was proved only on cytology and histopathology. There is a probability of this tumour undergoing malignant transformation. Therefore, these tumours need to be promptly diagnosed, adequately treated and should be included in the differential diagnosis of neck masses.